KOMODIFIKASI PERPUSTAKAAN KAFE SEBAGAI DAMPAK PERUBAHAN GAYA HIDUP URBAN - Koko Srimulyo; Meinia Prasyesti (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
The rise of cafes with various concepts is a response to the change that occurs in urban society today. What is meant by the change is the increasingly modern lifestyle of urban society. The lifestyle of urban communities, which is getting higher, has also caused cafe businesses increase. As a response to the urban lifestyle changes, many thematic cafes are now mushrooming. One of them is a library themed cafe, namely Libreria Eatery Cafe in Surabaya. Libreria Eatery combines a cafe as a place to eat and a library as a place to provide information and entertainment. Using a qualitative approach from the perspective of culture studies, this study observed the background of cafe business people who have commodified library that it turns into a libcafe as the impact of urban lifestyle change. The study found (1) the library was used as the interior design ornament of cafe, (2) the library was its main supporting business, (3) the library raised its image as modern entertaining information center.